Clinically Approved Drugs Inhibit the Staphylococcus aureus Multidrug NorA Efflux Pump and Reduce Biofilm Formation - Zimmermann, Saskia; Klinger-Strobel, Mareike; Bohnert, Jürgen A.; Wendler, Sindy; Rödel, Jürgen; Pletz, Mathias W.; Löffler, Bettina; Tuchscherr, Lorena (Frontiers in Microbiology, 2019)
Staphylococcus aureus has acquired resistances since the first use of antibiotics. NorA from S. aureus, an efflux pump belonging to the major facilitator superfamily, contributes to resistance to fluoroquinolones like ciprofloxacin, biocides, dyes, quaternary ammonium compounds, and antiseptics. Different compounds have been introduced as potential efflux pump inhibitors (EPIs) of NorA resulting in increased intracellular concentration of antibiotics, thus restoring their antibacterial activity and susceptibility. However, none of the currently known EPIs have been approved for clinical use, probably due to their toxicity profiles. In the present study, we screened approved drugs for possible efflux pump inhibition. By screening a compound library of approximately 1200 different drugs, we found that nilotinib, a tyrosine kinase inhibitor, showed the best results with a fractional inhibitory concentration index of 0.1875, indicating synergism with ciprofloxacin, and a minimum effective concentration as low as 0.195 µM. Moreover, 0.39 µM of nilotinib in combination with 8 µg/mL ciprofloxacin led to a significant reduction in biofilm formation and pre-formed mature biofilm. This is the first approved drug described that can be used as an efflux pump inhibitor and to reduce biofilm at clinically achievable concentrations.